2013
DOI: 10.1186/1476-0711-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, toxicological and antimicrobial evaluation of lawsonia inermis extracts against clinical isolates of pathogenic bacteria

Abstract: BackgroundThe emerging resistance of pathogen against the currently available antimicrobial agents demands the search of new antimicrobial agents. The use of medicinal plants as natural substitute is the paramount area of research to overwhelm the drug resistance of infectious agents. Scientists have not made enough effort on the evaluation of safety of medicinal plant yet.MethodsIn the present study antimicrobial activity of Lawsonia inermis is investigated against clinical isolates of seven bacteria includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 14 publications
6
37
1
Order By: Relevance
“…(Lawaly et al, 2017). The results of this study is in accordance with previous reports suggesting potent antibacterial activity of A. nilotica (Ali et al, 2017;Singh and Thakur, 2016;Gupta, 2015;Raghavendra et al, 2006), L. inermis Gull et al, 2013;Musa et al, 2011;Akter et al, 2010;Babu and Subhasree, 2009;Al-Rubiay et al, 2008;Nayak et al, 2007) and Z. jujube Linn (Elaloui et al, 2017;Arifa et al, 2016;Naz et al, 2013) against both gram negative and gram positive bacteria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(Lawaly et al, 2017). The results of this study is in accordance with previous reports suggesting potent antibacterial activity of A. nilotica (Ali et al, 2017;Singh and Thakur, 2016;Gupta, 2015;Raghavendra et al, 2006), L. inermis Gull et al, 2013;Musa et al, 2011;Akter et al, 2010;Babu and Subhasree, 2009;Al-Rubiay et al, 2008;Nayak et al, 2007) and Z. jujube Linn (Elaloui et al, 2017;Arifa et al, 2016;Naz et al, 2013) against both gram negative and gram positive bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…The result of this study conforms to earlier reports suggesting the presence of flavonoids, tannins, saponins, glycosides, steroids, terpenes and phenols in methanolic leaves extract on A. nilotica (Lawaly et al, 2017;Mrityunjoy et al, 2016;Singh and Thakur, 2016;Raghavendra et al, 2006), L. inermis (Rao et al, 2016;Gull et al, 2013;Nayak et al, 2007) and Z. jujube Linn (Elaloui et al , 2017;Mahajan and Chopda, 2009). In contrast, only Z. jujube Linn possessed volatile oils as reported by Kundu et al (1989).…”
Section: Discussionsupporting
confidence: 91%
“…Many studies on Lawsonia inermis leaves extractions showed that it had antibacterial activity against Gram [8][9][10]; and antifungal activity aganist (Candida albicans, Cryptococcus neoformans, A. niger and F. oxysporum) [11].…”
Section: Introductionmentioning
confidence: 99%
“…or death in first 2 hours and then after 24 hours. No sign of toxidrome were observed during in vivo toxicity evaluation in mice at 300 mg/kg concentration 36 .…”
Section: Miscellaneousmentioning
confidence: 90%
“…The minimum value of MIC for different bacterial strains ranged from 2.31 mg/ml to 9.27 mg/ml. At 1x MIC of each bacterial isolate, 3log 10 decrease in CFU was recorded after 6 hours of drug exposure and no growth was observed in almost all tested bacteria after 24 hours of exposure 36 .…”
Section: Analgesic and Antipyretic Activitymentioning
confidence: 93%